Records of beaked whales (family Ziphiidae) in Western Australian waters. (9th May 2014) - Groom, Christine J.; Coughran, Douglas K.; Smith, Holly C.
Abstract : Western Australia has an extensive coastline extending 12889 km (excluding islands) from latitude 35 degrees in the south to 14 degrees in the north. The extensive coastline intersects the distribution of many species of beaked whale. A total of 74 Ziphiidae were recorded as stranded along the Western Australian coast between 1940 and 2010 (70 years). Ten of the 21 species of beaked whales currently recognized taxonomically worldwide have been observed in Western Australia with True's beaked whale Mesoplodon mirus and Shepherd's beaked whale Tasmacetus shepherdi recorded more than elsewhere in Australia. Western Australia has the highest species diversity (10) of beaked whale strandings compared to other Australian states and regions. Gray's beaked whale, Mesoplodon grayi, was the most commonly reported species (33 records) and had the largest mass stranding group size (seven) of the beaked whales stranded in Western Australia. The records presented in this paper confirm the distribution of Arnoux's beaked whale Berardius arnuxii, strap-toothed beaked whale Mesoplodon layardii, Shepherd's beaked whale, Blainville's beaked whale Mesoplodon densirostris in Western Australian waters. The records presented of True's beaked whale confirm its presence in Australian waters, with Western Australia a possible key location for this species. Factors causing strandings and death should be investigated in future wherever possible, particularly the rostral injuries reported for six beaked whales. Beaked whale species identification should be confirmed through genetic analysis in future to maximize certainty of species identification.